Bioavailability, distribution and clearance of tracheally-instilled and gavaged uncoated or silica-coated zinc oxide nanoparticles - Konduru, Nagarjun V (Part Fibre Toxicol, 2014)
BACKGROUND: Nanoparticle pharmacokinetics and biological effects are influenced by several factors. We assessed the effects of amorphous SiO(2) coating on the pharmacokinetics of zinc oxide nanoparticles (ZnO NPs) following intratracheal (IT) instillation and gavage in rats. METHODS: Uncoated and SiO(2)-coated ZnO NPs were neutron-activated and IT-instilled at 1 mg/kg or gavaged at 5 mg/kg. Rats were followed over 28 days post-IT, and over 7 days post-gavage. Tissue samples were analyzed for (65)Zn radioactivity. Pulmonary responses to instilled NPs were also evaluated at 24 hours. RESULTS: SiO(2)-coated ZnO elicited significantly higher inflammatory responses than uncoated NPs. Pulmonary clearance of both (65)ZnO NPs was biphasic with a rapid initial t(1/2) (0.2 - 0.3 hours), and a slower terminal t(1/2) of 1.2 days (SiO(2)-coated ZnO) and 1.7 days (ZnO). Both NPs were almost completely cleared by day 7 (>98%). With IT-instilled (65)ZnO NPs, significantly more (65)Zn was found in skeletal muscle, liver, skin, kidneys, cecum and blood on day 2 in uncoated than SiO(2)-coated NPs. By 28 days, extrapulmonary levels of (65)Zn from both NPs significantly decreased. However, (65)Zn levels in skeletal muscle, skin and blood remained higher from uncoated NPs. Interestingly, (65)Zn levels in bone marrow and thoracic lymph nodes were higher from coated (65)ZnO NPs. More (65)Zn was excreted in the urine from rats instilled with SiO(2)-coated (65)ZnO NPs. After 7 days post-gavage, only 7.4% (uncoated) and 6.7% (coated) of (65)Zn dose were measured in all tissues combined. As with instilled NPs, after gavage significantly more (65)Zn was measured in skeletal muscle from uncoated NPs and less in thoracic lymph nodes. More (65)Zn was excreted in the urine and feces with coated than uncoated (65)ZnO NPs. However, over 95% of the total dose of both NPs was eliminated in the feces by day 7. CONCLUSIONS: Although SiO(2)-coated ZnO NPs were more inflammogenic, the overall lung clearance rate was not affected. However, SiO(2) coating altered the tissue distribution of (65)Zn in some extrapulmonary tissues. For both IT instillation and gavage administration, SiO(2) coating enhanced transport of (65)Zn to thoracic lymph nodes and decreased transport to the skeletal muscle.